Consumer perspectives of wine typicity and impact of region information on the sensory perception of Cabernet Sauvignon wines. (February 2022) - Souza Gonzaga, Lira; Bastian, Susan E.P.; Capone, Dimitra L.; Danner, Lukas; Jeffery, David W.
Graphical abstract: Highlights: Consumers are familiar with extrinsic factors related to the wine typicity concept. Origin information had a positive correlation with consumer preference scores. Influence of origin was higher when consumers were more familiar with the region. Regional profiles were evident according to rate-all-that-apply sensory results. Abstract: Region of origin is used in marketing of wine and by consumers as a wine quality indicator. To better understand wine consumers' purchase decisions, sensory perception, and wine liking in connection with wine provenance, this study used regular wine consumers (n = 112) to evaluate two Cabernet Sauvignon wines from each of four wine producing regions through hedonic rating and rate-all-that-apply (RATA) testing in conjunction with pre- and post-tasting questionnaires. The majority of consumers rated the region of origin stated on the label as important for purchase intent and for deciding the price they were willing to pay for a wine. The questionnaire also revealed that consumers were familiar with the wine typicity concept, but seemed to consider it only as an extrinsic characteristic rather than an intrinsic aspect of the wine. By randomly dividing the consumers into two groups (n = 56 each), one having information on the origin of samples and the other tasting without such knowledge, it was demonstrated that origin information had a positive impact on hedonic scores. Sensory profiling revealed that origin information did not impact the sample sensory characterisation, and liking for both groups was related to 'full body', 'jammy', and 'dark fruits' attributes. Some regional profile features were apparent for the samples, such as 'minty' for Coonawarra and savoury attributes for Bordeaux. Overall, this work highlighted that consumers could differentiate wines from distinct regions on the basis of sensory characteristics.